2009
DOI: 10.1007/s12565-009-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

An unusual variation of the flexor digitorum accessorius longus muscle—its anatomy and clinical significance

Abstract: In this article we describe a variant accessory muscle found in the deep posterior compartment of the leg in a 96 year-old female human cadaver. The flexor digitorum accessorius longus was found bilaterally, originating by two heads from the shafts of the tibia and fibula. The two heads of the muscle were observed to be subequal in size and none of the fleshy fibers of the muscle entered the tarsal tunnel. This stands in contrast with previous descriptions of accessory digital flexors, which are typically asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…There are several case reports incriminating the FDAL muscle, a variant of FDA, compromising the space in the tarsal tunnel and hence a causing tarsal tunnel syndrome [2][3][4][5][6]16]. As observed in the present study, the fleshy origin of medial head of FDA extended into the tarsal tunnel in majority of the cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…There are several case reports incriminating the FDAL muscle, a variant of FDA, compromising the space in the tarsal tunnel and hence a causing tarsal tunnel syndrome [2][3][4][5][6]16]. As observed in the present study, the fleshy origin of medial head of FDA extended into the tarsal tunnel in majority of the cases.…”
Section: Discussionsupporting
confidence: 71%
“…A variant of the FDA muscle named flexor digitorum accessorius longus (FDAL), which passes through the tunnel, has often been incriminated as a cause of TTS. When present, this muscle is believed to compress the tibial nerve [2][3][4][5][6]16].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the FDAL in the vicinity of the tarsal tunnel has recently been recognized as a type of space‐occupying lesion that can contribute to tarsal tunnel syndrome (Hwang and Hill, ; Lambert et al, ) and cause a variety of ankle pathologies (Bowers et al, ). The pain in the ankle after heavy physical exercise in the clinical cases in this study was also caused by the FDAL within the tarsal tunnel, which indicated that the FDAL within the tarsal tunnel can become hypertrophic because of frequent contractions.…”
Section: Discussionmentioning
confidence: 99%
“…However, most FDALs were present bilaterally in the present study, which suggests that the muscle usually has a contralateral counterpart. It has been reported to originate from the flexor retinaculum, transverse intermuscular septum, fibula, tibia, FHL, and flexor digitorum longus, and it inserts into the QP or tendon of the flexor digitorum longus (Peterson et al, ; Cheung et al, ; Gümüşalan and Kalaycioğlu, ; Deroy et al, ; Bowers et al, ; Hwang and Hill, ; Lambert el al., 2011). In the current study it arose from usual sites such as the flexor retinaculum, transverse intermuscular septum, and fibula, but all variants inserted into the QP and not into the tendon of the flexor digitorum longus.…”
Section: Discussionmentioning
confidence: 99%
“…There are also variations regarding volume and extension (Turner, 1867;Wood, 1868;Macalister, 1875;Testut, 1884;Driver & Denison, 1914;Lewis;Nathan et al, 1975;Nidecker et al, 1984;Bergman et al, 1988;Erickson et al;Sammarco & Stephens;Buckingham et al;del Sol et al;Gümüs¸alan & Kalayciog˘lu, 2000;Kurtoglu et al;Jaijesh et al 2006;Athavale et al, 2012). This muscle was first described by Meckel (Testut;Hwang & Hill, 2009 Sooriakumaran & Sivananthan;Georgiev et al, 2009). According to different research groups, this muscular variation is observed in some primitive mammals, as a posterior compartment muscle of the leg (Jaijesh et al; Testut; Turner; Nathan et al).…”
Section: Introductionmentioning
confidence: 99%